Measurement of the inclusive isolated-photon cross section in pp collisions at √s=13 TeV using 36 fb(-1) of ATLAS data - Aaboud, Morad; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Franchino, Silvia; Kugel, Andreas; Napolitano, Fabrizio; Schultz-Coulon, Hans-Christian; Spieker, Thomas; Stamen, Rainer; Starovoitov, Pavel; Weber, Sebastian; et al. (Journal of high energy physics, 2019)
The differential cross section for isolated-photon production in pp collisions is measured at a centre-of-mass energy of 13 TeV with the ATLAS detector at the LHC using an integrated luminosity of 36.1 fb(-1). The differential cross section is presented as a function of the photon transverse energy in different regions of photon pseudorapidity. The differential cross section as a function of the absolute value of the photon pseudorapidity is also presented in different regions of photon transverse energy. Next-to-leading-order QCD calculations from Jetphox and Sherpa as well as next-to-next-to-leading-order QCD calculations from Nnlojet are compared with the measurement, using several parameterisations of the proton parton distribution functions. The predictions provide a good description of the data within the experimental and theoretical uncertainties.
ATLAS collaboration*: Morad Aaboud, George Victor Andrei, Arthur Bolz, Monica Dunford, Silvia Franchino, Andreas Kugel, Fabrizio Napolitano, Hans-Christian Schultz-Coulon, Thomas Spieker, Rainer Stamen, Pavel Starovoitov, Sebastian Weber, Martin Wessels, Xiaoguang Yue [und 2921 weitere]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel ist die Ziffer "-1" hochgestellt
Gesehen am 04.06.2020